(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the role and importance of the comparative method in the educational process from a scientific pedagogical point of view. The comparative method is considered as an important methodological tool in the development of the ability to process knowledge. The article extensively covers the definitions of the comparative method, its tasks in educational activities and forms of practical application. Also, ways to increase the effectiveness of the use of the comparative method in higher education institutions and preschool educational organizations are proposed. The results of the study show that the systematic use of the comparative method significantly increases the skills of analytical thinking, critical assessment, and independent synthesis of knowledge in students and pupils. In addition, the integration of the comparative method with modern digital educational tools is separately studied, thereby revealing the possibilities of further enhancing the effectiveness of education. The positive impact of the comparative method on the educational process is substantiated based on empirical data through examples and analyses taken from pedagogical practice.